2012
DOI: 10.1007/s11904-012-0116-x
|View full text |Cite
|
Sign up to set email alerts
|

Treating Women with HIV: Is it Different than Treating Men?

Abstract: While antiretroviral therapy (ART) has had a tremendous impact on the morbidity and mortality of patients with HIV, there is evidence that many HIV-infected women experience treatment challenges that are different from men and these challenges are often associated with poorer outcomes. In the United States, blacks and Latino women are disproportionately affected by the HIV epidemic related to lack of access to high-quality HIV care, and socioeconomic factors. In Africa and Asia, HIV infection in women is affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…The identification of gender-specific challenges for women and for men is in line with research from other countries [33,34]. Healthcare workers should be trained to carefully take gender-related aspects into account in counseling and clinical care of TB/HIV patients.…”
Section: Barriers At the Patient/community Levelmentioning
confidence: 74%
“…The identification of gender-specific challenges for women and for men is in line with research from other countries [33,34]. Healthcare workers should be trained to carefully take gender-related aspects into account in counseling and clinical care of TB/HIV patients.…”
Section: Barriers At the Patient/community Levelmentioning
confidence: 74%
“…While the number of studies of the efficacy of HAART have been underpowered for the detection of sex differences, the aggregate data suggest that the men and women experience comparable responses to HAART in terms of CD4+ T-cells gain, rates of virologic suppression, and gains in survival. In 2012, Aziz and collaborators have shown sex differences often featured male and female groups with significant differences in timing of treatment initiation, adherence, concurrent conditions, and drug use (Aziz & Smith, 2012). In 2006, the Global Fund reported that Serbia had one of the lowest HIV testing rates, resulting in high percentage of persons diagnosed at a late stage of the disease (the joint United Nations Programme on HIV and AIDS; UNAIDS, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…When HAART first became available, women were less likely to be placed on therapy and were observed to have diminished therapeutic outcomes (Furler et al, 2006;Gandhi et al, 2002;Gebo et al, 2000;Gebo et al, 2001). Although more recent data suggest that these gaps have diminished in magnitude, concerns related to decreased access and quality of care for females still persist (Aziz & Smith, 2012;Collazos, Asensi, & Carton, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Health literacy was measured using the REALM test (score 0 to 60) with a higher score indicating a higher level of health literacy. Patient clinical variables were CD4 cell count ( £ 200 cells/mm 3 versus > 200 cells/mm 3 ), HIV RNA viral load ( £ 75 copies per milliliter versus > 75 copies per milliliter), receipt of antiretroviral medications, antiretroviral adherence in the last 3 days (100% versus < 100%), active substance and/or alcohol abuse, and presence of at least one comorbid medical condition. Degree of depressive symptoms was measured using the CES-D10 score (0 to 30), with a higher score indicating more depressive symptoms.…”
Section: Main Measuresmentioning
confidence: 99%
“…HIV-infected women account for about one quarter of persons living with HIV and have a unique set of health needs. [1][2][3][4][5] HIV-infected women are disproportionately African American and affected by poverty and its attendant consequences such as limited access to quality medical care. 1,2 Accumulating evidence has highlighted gender disparities in the receipt and quality of HIV care.…”
mentioning
confidence: 99%